Investigation of SHANK3 in schizophrenia. Issue 4 (28th March 2017) - de Sena Cortabitarte, Ana; Degenhardt, Franziska; Strohmaier, Jana; Lang, Maren; Weiss, Birgit; Roeth, Ralph; Giegling, Ina; Heilmann‐Heimbach, Stefanie; Hofmann, Andrea; Rujescu, Dan; Fischer, Christine; Rietschel, Marcella; et al.
Abstract : The postsynaptic scaffolding protein SHANK3 is essential for the normal function of glutamatergic synapses in the brain. Emerging evidence suggests that impaired plasticity of glutamatergic synapses contributes to the pathology of schizophrenia (SCZ). To investigate whether variants in the SHANK3 gene contribute to the etiology of SCZ, we sequenced SHANK3 in 500 affected individuals (cohort C1). In total, we identified 48 variants and compared them to European controls from the 1000 Genomes Project and the Exome Variant Server. Five variants showed significant differences in frequencies between patients and controls. We were able to follow three of them up in an independent cohort (C2) comprising 993 SCZ patients and 932 German controls. We could not confirm an association for three of these variants (rs140201628, rs1557620, and rs61729471). Two rare variants with predicted functional relevance were identified in further SCZ individuals of cohort C1: c.3032G>T (p.G1011V) and c.*27C>T. The latter variant was found in one additional SCZ individual and the p.G1011V variant was identified in two additional SCZ individuals from cohort C2. The p.G1011V variant was the most interesting variant in our study; together with previous studies this variant has been identified in 4 out of 1, 524 SCZ patients and in 4 out of 2, 147 individuals with autism spectrum disorder (ASD), but not in 2468 European Sanger‐sequenced controls. Therefore, we consider this variant a promising candidate variant for follow‐up studies in larger samples and functional investigations. © 2017 Wiley Periodicals, Inc.